2007
DOI: 10.1080/08990220701388364
|View full text |Cite
|
Sign up to set email alerts
|

Possible glutaminergic interaction between the capsule and neurite of Pacinian corpuscles

Abstract: The role of the capsule encasing the Pacinian corpuscle's (PC's) neurite, where mechanotransduction occurs, may be more than mechanical. The inner core of the PC's capsule consists of lamellar cells that are of Schwann-cell origin. Previously, we found both voltage-gated Na+ and K+ channels in these inner-core lamellae. Research on astrocytes and Schwann cells shows bidirectional signaling between glia and neurons, a major component of which is glutamate. Furthermore, Merkel cells show positive immunoreactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Strong evidence suggests that, in the Merkel cellneurite complex, the process relies on a synapselike mechanism (31,34,48,58), but the details are pending investigation. Similarly, a synapse-like communication between the neuron and lamellar cells also has been proposed to explain mechanosensitivity of Pacinian corpuscles (60,61).…”
Section: Cellular and Molecular Basis Of Mechanoreceptionmentioning
confidence: 97%
See 1 more Smart Citation
“…Strong evidence suggests that, in the Merkel cellneurite complex, the process relies on a synapselike mechanism (31,34,48,58), but the details are pending investigation. Similarly, a synapse-like communication between the neuron and lamellar cells also has been proposed to explain mechanosensitivity of Pacinian corpuscles (60,61).…”
Section: Cellular and Molecular Basis Of Mechanoreceptionmentioning
confidence: 97%
“…Similarly, lamellar cells in the Pacinian corpuscles (detectors of transient touch and high-frequency vibration) were proposed to influence excitability of the encapsulated afferent, which normally has a rapidly adapting firing pattern (60,61). The multi-component organization of sensory afferent and end-organs provides room for evolutionary changes to fine-tune mechanosensitivity to the species' needs.…”
mentioning
confidence: 99%
“…For the Pacinian corpuscle, studies in cats have revealed that inner-core lamellar cells have glutamate and γ-aminobutyric acid (GABA) receptors, vesicular glutamate transporters, synaptic proteins, synapse-like thickenings, and clear-core vesicles on both sides of the area adjacent to axonal filopodia and lamellae intersections. Glutamate and GABA receptor antagonists modulate electrophysiological responses of Aβ RA2-LTMRs (39, 40). These findings suggest that Pacinian corpuscle lamellar cells can modulate Aβ RA2-LTMR responses and potentially even transduce force directly.…”
Section: The Form That Underlies Function Of Cutaneous Touch Receptorsmentioning
confidence: 99%
“…Unlike VGLUT 2 , VGLUT 1 is only found in very few nerve fibers in the mouse colorectum [61], and in a small number of fibers in the urinary bladder, mostly within the muscular layers of this organ (Figure 3) [62]. Discrete VGLUT 1 expression has also been reported in the Pacinian corpuscle and associated neurites in the cat mesentery [55]. The disparate representation of VGLUT 1 and VGLUT 2 in peripheral nerves terminating in visceral organs is supported by Olsson et al [166], showing that ~3% of anterogradely traced guinea pig rectal nerve varicosities terminating in the myenteric plexus contain VGLUT 1 , whereas ~11% exhibit VGLUT 2 -Li.…”
Section: Expression Of Vgluts In Peripheral Visceral and Nonviscermentioning
confidence: 99%